Effect of high-fat diets on functional and biochemical parameters of the large intestine of rats - Bocharov, A. V. (Journal of Education, Health and Sport, 2017)
Aim: To determine the effect of high fat diet on the state of the colon. Materials and Methods: Edible fats with different fatty acid composition were used: usual (high linoleic) sunflower oil, high-oleic sunflower oil “Olivka”, high-palmitic oils: butter and palm oil, high- lauric coconut oil. These fats in the amount of 15% were added to the standard feed (5% fat). Rats were fed for 60 days. Every week, an indicator of the frequency of drfecations was determined. After euthanasia of animals, elastase, urease, lysozyme, catalase activity and MDA content were determined in the mucous membrane of the colon. The antioxidant- prooxidant index API was calculated by the ratio of catalase activity and MDA content, and the degree of dysbiosis according to A. P. Levitsky was calculated by the ratio of relative activities of urease and lysozyme. Results: Sunflower oil increases the number of defecations, butter, palm oil and, especially, coconut oil reduced the number of defecations, “Olivka” is not affected. In the mucous membrane of the colon, butter and palm oil increase the activity of elastase, urease, the degree of dysbiosis, the content of MDA and reduce the activity of lysozyme and the API index. The API also reduces by the usual sunflower oil and coconut oil. Conclusion: High- palmitic fats (butter and palm oil), cause the development of colitis, fats with a high content of saturated fatty acids (butter, palm and coconut oils) cause the development of dysbiosis in the colon mucosa by reducing lysozyme activity. High- oleic sunflower oil does not cause the development of colitis and dysbiosis.